Carbon uptake in response to climatic seasonality and time of day in Amazonian trees from different forest strata: the effect of shading on morning photosynthesis - Daniela Pereira Dias; Ricardo Antonio Marenco (Ciência Rural)
ABSTRACT: This study examined the effect of time of day and climatic seasonality on photosynthetic traits of canopy leaves from Amazonian trees of different forest strata. Photosynthetic traits and the Fv/Fm ratio were measured in the morning, at midday and in the afternoon, both in the dry and rainy seasons. Microclimatic data were obtained and the degree of shading estimated based on sunshine hours a tree received. The evaluated species and height of trees were: Coussapoa orthoneura (27.2 m tall), Mabea angularis (17.1 m), Goupia glabra (12.5 m) and Inga paraensis (8.4 m). In the dry season, in three of the four evaluated trees, light-saturated photosynthesis (Asat) was higher in the morning than in the afternoon. Whereas, in the rainy season, Asat was higher at midday or in the afternoon than in the morning in Mabea and Inga. In most trees, light and CO2-saturated photosynthesis (Amax) varied between times of day and climatic seasonality. In general, there was only a slight decline in the Fv/Fm ratio during the daylight hours, with the Fv/Fm ratio recovering to early morning values overnight. Morning irradiance was 34% lower in the rainy season than in the dry season, and in both seasons the morning temperature was about 3 °C below the daily mean. Diurnal and seasonal variations of Asat reflect the effect of stomatal conductance, as the Fv/Fm ratio consistently recovers overnight. In shaded trees, the morning photosynthesis is lower than in those that receive more sunlight, particularly in the rainy season when the morning irradiance is the lowest.